2010
DOI: 10.3109/00365591003709476
|View full text |Cite
|
Sign up to set email alerts
|

How do different tests evaluate sensation in the lower urinary tract?

Abstract: In patients with functional voiding disorders, the EPT can be disturbed independently of the bladder filling sensation. No significant correlation exists between volumes of filling sensations and bEPT (r < 0.005, p > 0.243). Therefore, both tests provide complementary information. Somatosensory tests of the pudendal nerve are correlated, so performing SSEP, pEPT and uEPT provides poor additional information to one of these tests alone. Somatosensory pudendal tests cannot be used to quantify filling sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Out of 80 studies, 61 exclusively applied CPTs [6,7,13–71], but four reported incomplete or no CPT results [14,32,61,64] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 80 studies, 61 exclusively applied CPTs [6,7,13–71], but four reported incomplete or no CPT results [14,32,61,64] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with neurological diseases or lesions such as diabetic neuropathy or spinal cord injury generally demonstrated higher CPTs compared to controls [7,26,28,29,30,31,32,78].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…La sensation de mauvaise vidange vésicale ne serait pas forcément en rapport avec le volume résiduel. De Laet et al ont récem-ment rapporté que chez les patients présentant des troubles du bas appareil urinaire, le seuil de perception électrique pouvait être modifié indépendamment de la sensation de réplétion vésicale [26]. Naoemova et al ont comparé l'éva-luation des sensations au remplissage vésicale pendant un examen urodynamique et les données du calendrier mictionnel sur trois jours en indiquant les différents besoins.…”
Section: Discussionunclassified